2017
DOI: 10.1103/physrevlett.118.197601
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Reversal of the Ferroelectric Polarization

Abstract: The ability to manipulate ferroelectrics at ultrafast speeds has long been an elusive target for materials research. Coherently exciting the ferroelectric mode with ultrashort optical pulses holds the promise to switch the ferroelectric polarization on femtosecond timescale, two orders of magnitude faster compared to what is possible today with pulsed electric fields.Here, we report on the demonstration of ultrafast optical reversal of the ferroelectric polarization in LiNbO 3 . Rather than driving the ferroel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 28 publications
(49 reference statements)
5
186
1
Order By: Relevance
“…The thus obtained potential would be appropriate for a very fast dynamics of the ferroelectric mode. At the same time, in the experiment [11] the characteristic time change of is not smaller than its inverse frequency. Moreover, the signal of the second harmonics vanishes at some point.…”
Section: Theoretical Approachmentioning
confidence: 74%
See 2 more Smart Citations
“…The thus obtained potential would be appropriate for a very fast dynamics of the ferroelectric mode. At the same time, in the experiment [11] the characteristic time change of is not smaller than its inverse frequency. Moreover, the signal of the second harmonics vanishes at some point.…”
Section: Theoretical Approachmentioning
confidence: 74%
“…2. In the experiment [11] for flu- Figure 3. Minimum of (normalized by ) as a function of fluence for different frequencies of the pump pulse.…”
Section: Calculation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear phononic effects can also create transient magnetic fields, thereby exciting magnetic excitations 131 . In the context of control over ferroelectrics, there is even a recent experiment that sees some indications of possible nonlinear-phononics-induced transient reversal 132 . For interested readers, who would like to know more on this subject, we refer to some recently published review articles in Refs.…”
Section: From Electronic Transitions In Solids To Vibrations In Molecmentioning
confidence: 99%
“…However the present sources do not provide the strength of a pulse sufficient for completely switching the polarization. Experiments [36] have shown that the reversal can be only 40% of its equilibrium value. Although the reversal is quite fast, occurring in about 10 −13 s, but the reversed polarization rapidly, during the same 10 −13 s, returns to the initial state, similarly to the dynamics induced by terahertz pulses, when the reversal happens over a picosecond time scale, followed by its fast complete retrieval [37].…”
Section: Introductionmentioning
confidence: 99%